Full‐face effects of temporal volumizing and temporal lifting techniques. (5th October 2020) - Casabona, Gabriela; Frank, Konstantin; Moellhoff, Nicholas; Gavril, Diana L.; Swift, Arthur; Freytag, David L.; Kaiser, Antonia; Green, Jeremy B.; Nikolis, Andreas; Cotofana, Sebastian
Abstract: Background: Most injection techniques utilizing hyaluronic acid–based soft tissue fillers have predictable outcomes at the location injected. However, the temporal region has been identified to have aesthetic effects beyond the temple. Aims: To identify and quantify the panfacial aesthetic effects of three different temporal injection techniques. Patients/Methods: The medical records of nine female and five male Caucasian patients with a mean age of 50.9 ± 11.9 years were retrospectively reviewed for the effects of these techniques: supraperiosteal, interfascial, and subdermal. Panfacial effects were evaluated by the semiquantitative assessment of aesthetic scores for the temple volume, the temporal crest visibility, the lateral orbital rim visibility, the position of the eyebrows, the severity of lateral canthal lines, the midfacial volume, and the contour of the jawline. Results: The supraperiosteal injection technique had the greatest influence on improving the temporal volume (25.0%), the temporal crest (33.3%), and the lateral orbital rim visibility (31.0%) scales but had no effects in other facial regions. The interfascial injection technique revealed good effects on improving temporal hollowing (23.3%) but had an even greater effect on the crow's feet (26.8%) and on the position of the eyebrow (33.3%). The subdermal injection technique had its greatest effects in the lower face by improving the contour of the jawline (26.8%) followed by the improvement of the lower cheek fullness scale (14.3%). Conclusion: Future injection algorithms could utilize all three injection techniques together as one multi‐layer injection approach with a tailored proportion of each technique based on the aesthetic needs of the patient.